1997
DOI: 10.1021/jf9609789
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linking of Milk Proteins with Transglutaminase at the Oil−Water Interface

Abstract: The influence of covalent cross-linking with transglutaminase on the time-dependent surface shear viscosity of adsorbed milk protein films at the n-tetradecane−water interface has been investigated for sodium caseinate, αs1-casein, β-casein, and β-lactoglobulin. Proteins were adsorbed from 10-3 wt % aqueous solutions at pH 7, and apparent surface viscosities were recorded at 40 °C in the presence of various enzyme concentrations. Results for casein systems showed a rapid enhancement in surface viscoelasticity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 24 publications
3
43
0
Order By: Relevance
“…The emulsifying properties of sodium caseinate are mainly due to its ability to lower the interfacial tension between oil and water phase. Faergemand et al (1997) found that incubation of sodium caseinate with TGase only slightly influences its emulsifying properties. The optimal size for microcapsules containing probiotics depends, however, on the intended purpose and on the type of food (McMaster et al, 2005).…”
Section: Formation and Characterization Of Casein Capsulesmentioning
confidence: 97%
“…The emulsifying properties of sodium caseinate are mainly due to its ability to lower the interfacial tension between oil and water phase. Faergemand et al (1997) found that incubation of sodium caseinate with TGase only slightly influences its emulsifying properties. The optimal size for microcapsules containing probiotics depends, however, on the intended purpose and on the type of food (McMaster et al, 2005).…”
Section: Formation and Characterization Of Casein Capsulesmentioning
confidence: 97%
“…At these low levels, these additives did not affect the thermal properties of WPI. When a specific incubation time was reached, the MTGase activity was inhibited by mixing an aliquot of 1 M stock solution of NH 4 Cl so that the final concentration of NH 4 Cl was 10 mM in the reaction dispersion (Faergemand, Murray, & Dickinson, 1997). In the case of '0 h' sample, NH 4 Cl was added to the reaction mixture soon after the addition of MTGase.…”
Section: Transglutaminase Treatmentmentioning
confidence: 99%
“…Crosslinking was reported to improve the mechanical properties and water stability [17]. Casein based materials have also been crosslinked with enzymes, especially transglutaminase [18,19]. Transglutaminase was found to substantially increase the molecular weights and mechanical properties of casein films [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Casein based materials have also been crosslinked with enzymes, especially transglutaminase [18,19]. Transglutaminase was found to substantially increase the molecular weights and mechanical properties of casein films [18,19]. Ultrasound processes were found to improve the mechanical strength of edible films developed from casein [20].…”
Section: Introductionmentioning
confidence: 99%